Anaplastic Lymphoma Kinase (ALK) Rearrangement of Lung Adenocarcinoma among North Sumatera Population - Putra, Muhammad Yusuf Adira; Soeroso, Noni Novisari; Syahruddin, Elisna; Suzanna, Evlina; Afiani, Dina; Ashar, Taufik; Lim, Darren Wan-Teck (Faculty of Medicine Universitas Airlangga, 2025)
Introduction: Lung cancer is a malignancy of the lung parenchyma or bronchi. Molecular targeted therapy directed at oncogene driver mutations, such as anaplastic lymphoma kinase (ALK), improves the prognosis of patients with non-small cell lung carcinoma (NSCLC). This study aimed to determine the characteristics of lung adenocarcinoma patients and the prevalence of ALK rearrangement among the North Sumatra population. Methods: This descriptive study used data from patients' formalin-fixed paraffin-embedded (FFPE) ALK examination results and medical records. The laboratory analyzed the patient’s FFPE for ALK fusion protein expression using the VENTANA anti-ALK (D5F3) procedure to determine the prevalence of ALK rearrangement. Results: Of the 34 subjects, it was revealed that the characteristics of lung adenocarcinoma patients were 18 patients aged >60 years old (52.9%), 26 male patients (76.4%), and 24 heavy smoker patients (70.6%). Based on the pathological tumor-node-metastasis (pTNM) stage, most samples were classified as stage IVA, with 24 cases (70.6%) showing the highest metastases to the pleura. There were 2 cases of ALK mutations obtained through immunohistochemical examination with a percentage of 5.8%. Conclusion: There are relatively few ALK rearrangement mutations in lung adenocarcinoma patients without screening. Additional research is needed to ascertain the distribution of lung adenocarcinoma patient characteristics associated with a higher prevalence of ALK rearrangement mutations.